Effect of Preconception Selenium Intake on the Risk for Gestational Diabetes: The Japan Environment and Children's Study - Hyo Kyozuka; Tsuyoshi Murata; Toma Fukuda; Akiko Yamaguchi; Aya Kanno; Shun Yasuda; Akiko Sato; Yuka Ogata; Mitsuaki Hosoya; Seiji Yasumura; Koichi Hashimoto; Hidekazu Nishigori; et al. (MDPI AG, 2021)
Selenium (Se) acts as a cofactor of antioxidant enzymes. Preconception care may reduce the risk of gestational diabetes mellitus (GDM). We examined the association between preconception Se intake and the risk of GDM in Japanese women. Using the Japan Environment and Children's Study database, we identified 92,764 Japanese women recruited between January 2011 and March 2014. Participants were categorized into five groups according to preconception Se intake quintiles (Q1 and Q5 were the lowest and highest Se intake groups, respectively). GDM was categorized as early-onset (Eo-GDM) or late-onset (Lo-GDM) diagnosed before or after 24 weeks, respectively. Multiple logistic regressions were performed to identify the effect of preconception Se intake on GDM, Eo-GDM, and Lo-GDM. Using Q3 (the middle Se intake group) as the reference, a multiple logistic regression analysis showed that the highest (Q5) Se intake group demonstrated increased risks of GDM (adjusted odds ratio (aOR): 1.15, 95% confidence interval (CI): 1.01-1.30) and the lowest (Q1) Se intake group had increased risks of Lo-GDM (aOR: 1.19, 95% CI: 1.01-1.41). Thus, both high and low preconception Se intakes increase risks of glucose intolerance during pregnancy. This finding may indicate new recommendations for preconception Se intake to prevent GDM.